2009
DOI: 10.1038/jhg.2009.6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic sequence variations of BRCA1-interacting genes AURKA, BAP1, BARD1 and DHX9 in French Canadian Families with high risk of breast cancer

Abstract: Breast cancer is a heterogeneous disease displaying some degree of familial clustering. Highly penetrant breast cancer susceptibility genes represent approximately 20-25% of the familial aggregation of breast cancer. A significant proportion of this familial aggregation of breast cancer is thus yet to be explained by other breast cancer susceptibility genes. Given the high susceptibility conferred by the two major breast cancer predisposition genes, BRCA1 and BRCA2 and the implication of these genes in many ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 56 publications
2
34
1
Order By: Relevance
“…Pervious studies have described that no signiWcant associations were found between Cys577Ser mutation and breast cancer risk in Poland, Canada, Sweden, and Australia (Gorringe et al 2008;Jakubowska et al 2008;Guénard et al 2009;Johnatty et al 2009;Ratajska et al 2011). The discrepancy between the present studies could be due to the population controls used, which may have resulted in a positive association by chance.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Pervious studies have described that no signiWcant associations were found between Cys577Ser mutation and breast cancer risk in Poland, Canada, Sweden, and Australia (Gorringe et al 2008;Jakubowska et al 2008;Guénard et al 2009;Johnatty et al 2009;Ratajska et al 2011). The discrepancy between the present studies could be due to the population controls used, which may have resulted in a positive association by chance.…”
Section: Discussioncontrasting
confidence: 75%
“…A total of nineteen studies with full-text articles examined the association of Cys557Ser mutation with breast cancer were found (Thai et al 1998;Ghimenti et al 2002;Karppinen et al 2004;Tarasov et al 2006;Onay et al 2006;Vahteristo et al 2006;Stacey et al 2006;Karppinen et al 2006;Gorringe et al 2008;Jakubowska et al 2008;Guénard et al 2009;Johnatty et al 2009;Spurdle et al 2011;Ratajska et al 2011). Among them, the study of Karppinen et al was excluded because they investigated almost the same population reported before.…”
Section: Eligible Studies and Meta-analysis Databasesmentioning
confidence: 97%
See 1 more Smart Citation
“…The possibility remains that the N-terminal dsRBD(s) interact with distal RHA domains; future experiments to test this model are warranted. The results will contribute to understanding the essential role of RHA in normal cells and the apparent contribution of RHA dysfunction to neoplastic growth (35)(36)(37). The outcomes will fuel fundamental understanding of RNA helicases across cell biology and at the virushost interface.…”
Section: Discussionmentioning
confidence: 99%
“…In support of BAP1 functioning as a tumor suppressor, several recent publications have identified BAP1 mutations in various forms of cancer (31)(32)(33)(34)(35)(36). Germline mutations in BAP1 have been shown to predispose patients to uveal melanoma, lung carcinoma, meningioma, and melanocytic tumors (31)(32)(33)(34)(35)(36). BAP1 is also commonly inactivated by somatic mutations and/or its location on chromosome 3p21.1 is lost in malignant pleural mesotheliomas (MPM; ref.…”
Section: Introductionmentioning
confidence: 99%